Epidemiology of cervix cancer in Brazil (2005-2015): study of mortality and hospital intervention rates - Kuiava, Victor Antônio; Chielle, Eduardo Ottobelli (Archives in Biosciences & Health, 2019)
Cervical neoplasia has high morbidity and mortality and is the main female gynecological neoplasia, but it is susceptible to early detection and cure. A major challenge for developing countries such as Brazil is the expansion of prevention programs, which becomes more effective when the epidemiology is known. The objective of this study was to conduct an epidemiological survey to evaluate the Brazilian panorama of this neoplasm. A temporal aggregate study was performed using the mortality and hospital admission rates for cervical neoplasia throughout the Brazilian territory during the years 2005 to 2015, data obtained through DATASUS and IBGE. During the years 2005 to 2015, there was a significant drop (p<0.05) in hospital admission rates in the 0-19, 20-39, 40-59, 60-79 years, with an average fall of 36 % and a death increase in the age group 20-39 years. The North region had a significant increase in death in the range ≥ 80 years, 140%, p<0.02. The mean mortality rate in Brazil was 5.14, with a 95% CI of 5.01 to 5.27. Cervical neoplasia is still present in Brazil, although mortality has a tendency to decrease, this tendency is unequally distributed in Brazil, with the north and northeast regions showing the highest rates. Better public policies are fundamental.